Efektivitas Model Pembelajaran Grup Investigation Ditinjau Dari Kemampuan Berfikir Kritis Siswa Pada Mata Pelajaran PPKN Kelas V Di SD Kasongan - Trisna , Dika Ayu; Wibowo, Ari (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effectiveness applying the group investigation model in terms of critical thinking skills the fifth grade student at SD Kasongan. This type research an experimental research with true experimental design. The subject this study were student of class VA and VB SD Kasongan. This research data collection methods include documentation and test methods. The instruments used in study were tes (pretest and postest) and student activity observation sheet. Data analysis used descriptive statistics which included validity test, reliability, normality, homogeneity, N-Gain Score hypothesis test which included dependent sample t-test and independen sample t test. -test. The result this study indicate that: (1) The group investigation learning method has proven effective in increasing student critical thinking skills in Civics subjects; (2) There are differences in the learning outcomes of student who used the group investigation learning method and those who used conventional learning methods.